Makna Pesan Lagu “Pilu Membiru”,“Rehat”DAN“SULUNG”Karya Kunto Aji - Pita Sari (DIGICOM : Jurnal Komunikasi dan Media, 2022)
The Semiotic Analysis of the Meaning of the Messages of the Lyrics of the Song "Pilu Membiru", "Rehat", and "Sulung" by Kunto Aji was written and researched using semiotic theory according to Ferdinand de Saussure to reveal the meaning and message of the lyrics of the song by singer Kunto Aji entitled Pilu Membiru, Rest, and Eldest. The song is contained in Kunto Aji's second album entitled MantraMantra, where the presence of this album is intended to self-healing the listeners so that they can interpret life positively. The subject of the research is Kunto Aji as a singer. The data collection technique used in this research is qualitative analysis, the data obtained from the analysis of lyrics according to Ferdinand de Saussure's theory, which will then provide an overview of the meaning of the message contained in the lyrics of the song. From the results of this study, it can be concluded that the three songs of Kunto Aji in the MantraMantra album have a message not to give up in life and always think positively. The three songs are also delivered in the same pattern,which is repetitive to instill the meaning of the lyrics in the listener's subconscious.